1997
DOI: 10.1021/bi971797i
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of the Copper-Containing Amine Oxidase from Arthrobacter globiformis in the Holo and Apo Forms:  Implications for the Biogenesis of Topaquinone,

Abstract: The crystal structures of the copper enzyme phenylethylamine oxidase from the Gram-positive bacterium Arthrobacter globiformis (AGAO) have been determined and refined for three forms of the enzyme: the holoenzyme in its active form (at 2.2 A resolution), the holoenzyme in an inactive form (at 2.8 A resolution), and the apoenzyme (at 2.2 A resolution). The holoenzyme has a topaquinone (TPQ) cofactor formed from the apoenzyme by the post-translational modification of a tyrosine residue in the presence of Cu2+. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
405
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(428 citation statements)
references
References 32 publications
21
405
2
Order By: Relevance
“…The interaction may be either electrostatic or hydrophobic or both. In AGAO, the molecular surface surrounding the entrance to the active-site channel is predominantly negative (25). A wire with a Ru(II) head group (charge ϩ2) should bind better than one with a Re(I) head group (charge ϩ1) or a wire with no head group, as observed.…”
Section: Crystal Structure Of the [Ru(ii)phen-c4-dma]-agao Complexmentioning
confidence: 69%
See 2 more Smart Citations
“…The interaction may be either electrostatic or hydrophobic or both. In AGAO, the molecular surface surrounding the entrance to the active-site channel is predominantly negative (25). A wire with a Ru(II) head group (charge ϩ2) should bind better than one with a Re(I) head group (charge ϩ1) or a wire with no head group, as observed.…”
Section: Crystal Structure Of the [Ru(ii)phen-c4-dma]-agao Complexmentioning
confidence: 69%
“…There is no deviation from the crystallographic twofold symmetry of the molecule, and the present crystallographic data do not permit us to conclude whether the two channels are occupied symmetrically. Within the limits of precision, the structure of the protein in the wire complex is identical to the structure of the native protein (25). The TPQ ring, which is disordered in many CuAO structures and is bound to the Cu atom in some of them, is fully ordered in the off-Cu position.…”
Section: Crystal Structure Of the [Ru(ii)phen-c4-dma]-agao Complexmentioning
confidence: 95%
See 1 more Smart Citation
“…Crystal structures of des (1-52) grancalcin revealed that Ca 2+ -dependent conformational change is very small, and it is thought that the N-terminal Gly/Pro-rich region is required for the conformational change. A second example, copper enzyme phenylethylamine oxidase (PDB 1AV4), also shows a drastic reduction of B factors in almost all of its residues upon Cu 2+ and topaquinone cofactor binding (Wilce et al, 1997). The structures of the apo-and holoenzymes used for comparison have both been determined at 2.2 Å resolution, and the overall rms difference between them is 0.4 Å These examples indicate that local ligand binding can change the B factors of the residues distant from the binding sites.…”
Section: E Vidence That C a 2 + Ions Function To Tighten Structural Mmentioning
confidence: 99%
“…Knowledge concerning the physiological role, mechanism of action [1][2][3][4] and numerous X-ray structures [5][6][7][8][9][10][11][12][13][14] of these enzymes, as well as methods for protein expression of CAOs, 15 making larger quantities of protein samples available, which is useful for various experiments, has grown progressively in the past two decades.…”
Section: Introductionmentioning
confidence: 99%